Dilema Kewargaan Kelompok Minoritas:: Studi Kasus Suku Bajo di Nusa Tenggara Timur - Sastrawati, Nila; Bakar, Abu (Jurnal Masyarakat dan Budaya, 2025)
This paper discusses the issue of citizenship of the Bajo ethnic minority group on Kera Island, Kupang Regency, East Nusa Tenggara Province. The general question in this study is what are the implications of state politics for citizenship in the case of the Bajo tribe on Kera Island?. To answer this question, the concept of citizenship is used as an analytical tool. This research uses qualitative research, with a case study research design. This research concludes that the Bajo people as a minority group in East Nusa Tenggara find themselves in a dilemma. On the one hand, the state considers the Bajo people on Kera Island as squatters who are not entitled to citizenship status, therefore they do not get their rights, especially with regard to basic services. But on the other hand, the Bajo people are still involved in the electoral process to determine people’s representatives. In this condition, the Bajo people feel that their citizenship status is only given as long as it relates to the interests of the state and is forgotten again when the state no longer has an interest.